C++ Programming - Malik, D.S
C++ Programming: From Problem Analysis to Program Design, Third Edition is the ground-breaking, definitive text for the CS1 course. Best-selling author D.S. Malik employs a student-focused approach, using complete programming examples to teach introductory programming concepts. This third edition has been enhanced to further demonstrate the use of OOD methodology, to introduce sorting algorithms (bubble sort and insertion sort), and to present additional material on abstract classes. In addition, the exercise sets at the end of each chapter have been expanded, and now contain several calculus and engineering-related exercises. Finally, all programs have been written, compiled, and quality-assurance tested with Microsoft Visual C++ .NET, available as an optional compiler with this text